2006
DOI: 10.1111/j.1365-2958.2006.05081.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the flagellar filament and the role of motility in bacterial prey‐penetration by Bdellovibrio bacteriovorus

Abstract: SummaryThe predatory bacterium Bdellovibrio bacteriovorus swims rapidly by rotation of a single, polar flagellum comprised of a helical filament of flagellin monomers, contained within a membrane sheath and powered by a basal motor complex. Bdellovibrio collides with, enters and replicates within bacterial prey, a process previously suggested to firstly require flagellar motility and then flagellar shedding upon prey entry. Here we show that flagella are not always shed upon prey entry and we study the six fli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
192
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(199 citation statements)
references
References 26 publications
7
192
0
Order By: Relevance
“…5a) were seen, by microscopy, to attach to and invade prey and form bdelloplasts at the same rate; a finding confirmed by the use of the luminescent predation assay (Lambert et al, 2003(Lambert et al, , 2006 which showed that the initial prey death was equal for both the wild-type and tatA1 Bd mutant B. bacteriovorus strains (data not shown). The wildtype B. bacteriovorus lysed the bdelloplasts after 4 h in synchronous cultures (Fig.…”
Section: Prediction and Expression Of Potentialmentioning
confidence: 54%
See 3 more Smart Citations
“…5a) were seen, by microscopy, to attach to and invade prey and form bdelloplasts at the same rate; a finding confirmed by the use of the luminescent predation assay (Lambert et al, 2003(Lambert et al, , 2006 which showed that the initial prey death was equal for both the wild-type and tatA1 Bd mutant B. bacteriovorus strains (data not shown). The wildtype B. bacteriovorus lysed the bdelloplasts after 4 h in synchronous cultures (Fig.…”
Section: Prediction and Expression Of Potentialmentioning
confidence: 54%
“…Furthermore, it is likely that there are some TatBCA2-specific substrates that are essential for B. bacteriovorus viability in both growth modes. The very slow axenic growth phenotype of a single tatA/E homologue is unprecedented, even more so given the high levels of gene redundancy seen in other dual orthologous gene systems in B. bacteriovorus (Lambert et al, 2006;Rendulic et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We studied the bacterial predator Bdellovibrio bacteriovorus preying upon Escherichia coli. Bdellovibrio bacteriovorus is a small (0.4 Â 1 mm) and highly motile (it can swim over 160 mm s 21 , or 160 body lengths per second [22]) predator of Gramnegative bacteria, that occurs, for example, in soil, in the human gut and in water [23]. To complete its life cycle, B. bacteriovorus inserts itself into the periplasmic space of its prey and converts it into a round-shaped 'bdelloplast' [24].…”
Section: Introductionmentioning
confidence: 99%